Efektivitas Penggunaan Video Stop Motion Dalam Menentukan Nilai Sebagai Implementasi Pembelajaran Teks Hikayat - Hasminur, Hasminur; Charlina, Charlina; Sinaga, Mangatur (Cetta: Jurnal Ilmu Pendidikan, 2024)
The aim of this research, which was carried out using a quasi-experimental design, was to determine whether the different variables used were successful or not. This research aims to determine the effectiveness of using stop motion video in determining grades as an implementation of saga text learning in SMA/SMK/MA. This research is a quasi-experiment. The effectiveness of using stop motion video in determining grades as an implementation of saga text learning in SMA/SMK/MA between classes that were treated using stop motion video and without using stop motion video. Written tests and multiple choice exams were used to evaluate success in this research. Both the experimental class which was treated using stop motion video to determine the value of the saga, and the control class who were not treated were given this test before and after the learning process was carried out. The results of this research show that the experimental group treatment which used stop motion video to determine the value of the saga was superior to the control group treatment which did not use stop motion video.